System Modeling to Optimize the Production Quantity of Men's and Women's Jackets and Achieve Maximum Profit: A Case Study at Konveksi ABC Cikarang Using Linear Programming - Aji, Wisnu; Agustina Kurniawati, Dwi; Saif Muhammad Mussafi, Noor (Journal of Industrial Engineering and Halal Industries, 2025)
This study aims to develop an optimal production strategy for Konveksi Jaket ABC Cikarang, a garment manufacturer specializing in men's and women's jackets. The company faces significant challenges in resource allocation, particularly in managing limited material supplies and production capacity. To address this, a Linear Programming approach is applied to determine the most profitable production combination. The model incorporates two decision variables representing the quantities of men's and women's jackets and is constrained by real-world resource limitations. The objective function is designed to maximize profit, and the model is solved using IBM ILOG CPLEX software. The results indicate that the optimal production decision is to produce 125 units of women’s jackets and none of the men’s jackets, resulting in a maximum profit of IDR 8,125,000. These findings demonstrate that mathematical optimization can serve as an effective decision-support tool for improving production planning and efficiency in resource-constrained environments.